Antitumor effects and cytotoxicity of recombinant plant nucleases - Matousek, Jaroslav; Podzimek, Tomás; Poucková, Pavla; Stehlík, Jan; Skvor, Jirí; Soucek, Josef; Matousek, Josef (Oncology research, 2009)
Recombinant plant nucleases R-TBN1 and R-HBN1 were isolated to homogeneity and examined for their antitumor effects and cytotoxicity. Although antiproliferative effects of both recombinant nucleases were not significant on the ML-2 cell culture in vitro, the nucleases were strongly cytostatic in vivo after their administration intravenously as stabilized conjugates with polyethylene glycol (PEG). Recombinant nucleases were as effective against melanoma tumors as previously studied pine pollen (PN) and mung bean nucleases and their effects were reached at about 10 times lower concentrations compared to the use of bovine seminal RNase (BS-RNase). Because the recombinant nucleases R-HBN1 and R-TBN1 share only 67.4% amino acid identity and showed only partial immunochemical cross-reactivity, their similar anticancerogenic effects can be mainly explained by their catalytical similarity. Both recombinant nucleases showed lower degree of aspermatogenesis compared to BS-RNAse and PN nuclease. Unlike BS-RNase, aspermatogenesis induced by both recombinant nucleases could not be prevented by the homologous antibody complexes. Owing to relatively low cytotoxicity on the one hand, and high efficiency at low protein levels on the other, recombinant plant nucleases R-HBN1 and R-TBN1 appear to be stable biochemical agents that can be targeted as potential antitumor cytostatics.
Keywords: Spermatogenesis; myeloidní leukemie; Cattle; lidé; Cell Proliferation; Endonucleases; Leukemia, Myeloid; skot; Antineoplastic Agents; endonukleasy; nádorové buňky kultivované; protinádorové látky; myši; Humans; myši nahé; Melanoma; spermatogeneze; Solanum lycopersicum; Mice; Mice, Nude; proliferace buněk; melanom; mužské pohlaví; Glycosylation; zvířata; glykosylace; rekombinantní proteiny; Recombinant Proteins; Animals; Male; Tumor Cells, Cultured; Humulus